2016
DOI: 10.1093/ndt/gfw205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral versus intravenous vitamin D receptor activator in reducing infection-related mortality in hemodialysis patients: the Q-Cohort Study

Abstract: Treatment with intravenous VDRA more effectively reduces the incidence of mortality from infection than oral VDRA in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…At the moment, no interventional study showed any survival advantage for CKD and dialysis patients using native vitamin D supplementation. Tanaka et al reported that infection-related mortality in Japan is reduced in patients receiving VDRA mostly intravenously [106]. In a recent meta-analysis of CKD, Li et al reported that VDRAs reduced the incidence of cardiovascular events and reduced proteinuria, but resulted in an increased probability of hypercalcemia when paricalcitol was used [107].…”
Section: Vdra For Ckd and Dialysis Patientsmentioning
confidence: 99%
“…At the moment, no interventional study showed any survival advantage for CKD and dialysis patients using native vitamin D supplementation. Tanaka et al reported that infection-related mortality in Japan is reduced in patients receiving VDRA mostly intravenously [106]. In a recent meta-analysis of CKD, Li et al reported that VDRAs reduced the incidence of cardiovascular events and reduced proteinuria, but resulted in an increased probability of hypercalcemia when paricalcitol was used [107].…”
Section: Vdra For Ckd and Dialysis Patientsmentioning
confidence: 99%
“…Accordingly, our data should be interpreted cautiously based on the historical context described above. In addition, because VDRAs were shown to exert protective effects against infection-related death in hemodialysis patients 15 , our data suggest that the dose of VDRAs for treatment of secondary hyperparathyroidism should be adjusted cautiously to avoid induction of VDRA-related hypercalcemia.…”
Section: Discussionmentioning
confidence: 91%
“…The present study aimed to determine whether serum calcium level is associated with risk of infection-related death in hemodialysis patients. To achieve this aim, we analyzed the dataset in the Q-Cohort Study, a multicenter, prospective, observational study of hemodialysis patients in Japan [14][15][16] .…”
mentioning
confidence: 99%
“…The 5 hazards ratios (HRs) calculated in each stratum were combined into an overall treatment effect [10]. Matched pairs were constructed using the greedy matching algorithm with a caliper width of 0.2 SDs of the logit of the propensity score, at a ratio of 1: 1 without replacement [11, 12]. Statistical analysis was performed using commercially available software (JMP Statistics version 11.0; SAS Institute, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%